Mexico : 2018 Article IV Consultation-Press Release; Staff Report; and Staff Statement. (IMF Staff Country Reports; Country Report ;, 2018)
A new political landscape is shaping up in Mexico following the July elections. President-elect Lopez Obrador has promised to reduce corruption and crime, and boost social spending and public investment, while maintaining fiscal prudence. The incoming administration will inherit an economy with very strong fundamentals and policy frameworks that has exhibited resilience in the face of a complex external environment. But Mexico still confronts significant challenges-namely to strengthen growth while reducing poverty and inequality-and has yet to win the fight against corruption and crime. At the same time, uncertainty associated with the global economic environment and the policies of the incoming administration persists. Prospects hinge on the steadfast implementation of structural reforms while ensuring continued macroeconomic stability.